2013
DOI: 10.1002/jgrc.20076
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of river water and local sea‐ice melting on the Laptev Sea shelf (Siberian Arctic)

Abstract: [1] Hydrographic and stable isotope (d 18 O) data from four summer surveys in the Laptev Sea are used to derive fractions of sea-ice meltwater and river water. Sea-ice meltwater fractions are found to be correlated to river water fractions. While initial heat of river discharge is too small to melt the observed 0-158 km 3 of sea-ice meltwater, arctic rivers contain suspended particles and colored dissolved organic material that preferentially absorb solar radiation. Accordingly, heat content in surface waters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 56 publications
3
53
1
3
Order By: Relevance
“…In agreement with our result, Zhang et al [32] observed an increased moisture transport into the Eurasian river basins, and Shiklomanov and Lammers [50] described a peak river discharge in 2007. Some authors have suggested a link between increased Eurasian river discharge and sea ice decline [25,26]. This relationship is in accordance with our own results, given the important sea ice retreat that occurred to the north of the main Eurasian Arctic river estuaries in 2006/2007 (Figure 1).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with our result, Zhang et al [32] observed an increased moisture transport into the Eurasian river basins, and Shiklomanov and Lammers [50] described a peak river discharge in 2007. Some authors have suggested a link between increased Eurasian river discharge and sea ice decline [25,26]. This relationship is in accordance with our own results, given the important sea ice retreat that occurred to the north of the main Eurasian Arctic river estuaries in 2006/2007 (Figure 1).…”
Section: Discussionsupporting
confidence: 92%
“…The recent change in the perennial sea ice [22,23] is considered one of the most important reasons for the decrease in sea ice volume by several authors. However, variations in the hydrological cycle can affect sea ice too, and in some reports the reduction in sea ice has been related to increased river discharge [24][25][26] or storm activity [27,28]. Atmospheric moisture transport has an important role in sea ice extent variations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dmitrenko et al, 2010). Given that the negative SIM signal on the Laptev Sea is -to a large extent -the result of winter sea-ice formation within the coastal polynyas, the shelf waters containing a negative SIM signal at salinity of 30 to 32 found at ∼ 30 m water depth are fed by bottom waters in the central Laptev Sea (Bauch et al, 2012.…”
Section: Laptev Sea Sim Signal and F Sim /F R Signaturementioning
confidence: 99%
“…Sampling procedure and data analysis are described in detail by Bauch et al (2010Bauch et al ( , 2013. The combined interpretation of δ 18 O composition of the water and salinity allows for the quantification of the different freshwater contributions in polar regions, i.e.…”
Section: Riverine Fraction Of Sea Watermentioning
confidence: 99%